A novel class of selective non-nucleoside inhibitors of human DNA methyltransferase 3A. (15th May 2021) - Huang, Sunzeyu; Stillson, Nathaniel J.; Sandoval, Jonathan E.; Yung, Chitoh; Reich, Norbert O.
Graphical abstract: Abstract: Screening of a small chemical library ( Medicines for Malaria Venture Pathogen Box) identified two structurally related pyrazolone (inhibitor 1) and pyridazine (inhibitor 2) DNMT3A inhibitors with low micromolar inhibition constants. The uncompetitive and mixed type inhibition patterns with DNA and AdoMet suggest these molecules act through an allosteric mechanism, and thus are unlikely to bind to the enzyme's active site. Unlike the clinically used mechanism based DNMT inhibitors such as decitabine or azacitidine that act via the enzyme active site, the inhibitors described here could lead to the development of more selective drugs. Both inhibitors show promising selectivity for DNMT3A in comparison to DNMT1 and bacterial DNA cytosine methyltransferases. With further study, this could form the basis of preferential targeting of de novo DNA methylation over maintenance DNA methylation.